Suppression history of distractor location biases attentional and oculomotor control. Issue 2 (7th February 2019) - Di Caro, Valeria; Theeuwes, Jan; Della Libera, Chiara
ABSTRACT: Past selection experience greatly affects the deployment of attention such that targets are more readily selected if their features or locations were more frequently selected in the past. Crucially, recent studies have shown similar experience-dependent effects also for salient task irrelevant stimuli: distractors exerted less interference if they appeared at a location where they were presented more often, relatively to other possible locations. Here we investigated the effects of such suppression history on the immediate behavioural correlates of attentional deployment, i.e., eye movements. Participants were to make saccadic eye movements to a target stimulus, while ignoring a highly distracting irrelevant visual onset appearing abruptly on the screen in a proportion of trials. Crucially, this irrelevant onset occurred more frequently in two locations on the visual display and our results showed that, relatively to distractors elsewhere, onsets presented at these locations became easier to ignore, giving rise to reduced oculomotor capture. Consistent with the notion that experience can alter attentional deployment towards spatial locations, these findings indicate that, through learning, the priority of high frequency locations becomes suppressed, attenuating the intrinsic saliency of distractors appearing therein. Traces left by individual events of attentional suppression decrease the processing priority of coordinates within topographic maps of the visual space.